Effect of chronic high-intensity exercise on hunger and satiation and levels of acylated ghrelin and leptin in women - Koshki Mahmoud Hesar; Mollanovruzi Azam; Lamir Amin Rashid (Sciendo, 2018)
Study aim: The purpose of this study was to investigate the effect of chronic high-intensity exercise training on hunger, satiation, related hormones and weight loss among women who are obese or overweight. Material and methods: The sample group was composed of 25 subjects, divided into two groups: a high-intensity exercise group (n = 15) intensity of 80-90% of maximum heart rate and a non-training control group (n = 10). The blood sample test was performed in two stages of rest, fasted state and before breakfast and an appetite questionnaire was completed. The training procedure was a high-intensity exercise, three sessions a week for twelve weeks and two hours after breakfast. Independent and dependent t-tests were used to analyze the data. Results: The results showed that high-intensity exercise caused a significant loss of weight (p = 0.01) and fat percentage (p = 0.001) and plasma insulin levels (p = 0.03), but it had no effect on hunger and satiation, calorie intake or plasma leptin. Also, it significantly increased the plasma acylated ghrelin (p = 0.04) and maximum oxygen consumption (p < 0.001). Conclusions: Based on the results of this study, it can be noted that high-intensity exercise is suitable for weight loss and not increasing hunger. The lack of calorie intake along with weight loss showed that negative energy balance caused no appetite compensatory responses. Also, high-intensity exercise stimulates physiological responses to increase appetite, but it did not affect the feeling of appetite. In other words, changes in mental and physiological appetite because of high-intensity exercise do not match.